IMPLEMENTASI KEBIJAKAN BELAJAR DARI RUMAH PADA MASA COVID 19 TINGKAT SEKOLAH MENENGAH PERTAMA DI KECAMATAN BABELAN - Umi Hafilda; Adi Susila (Governance, 2022)
Electronic learning is an important instrument in online learning in this time of covid. As an effort to encourage the prevention of the Covid-19 virus in the world of education, the Ministry of Education and Culture issued Circular Letter No. 15 of 2020 regarding guidelines for organizing learning from home in an emergency period of the spread of Covid-19. The Bekasi Regency Government has implemented Circular No. 15 of 2020 and formed derivative regulations, namely: Circular No. 420/SE-37/DISDIK/2020. However, in its implementation it is still considered not optimal due to many obstacles in implementing this policy. The aims of this research are 1. To analyze the implementation of the learning from home policy, 2. to analyze the supporting and inhibiting factors for the implementation of the learning from home policy at the junior high school level in Babelan District. The researcher examines this case using the constructivism paradigm with qualitative research methods accompanied by a case study research approach. Based on the results of the research that the implementation of the policy of learning from home at the junior high school level in the Babelan sub-district, Bekasi Regency is running well which is influenced by several supporting factors, namely: Availability of Regulations, The establishment of cooperation between internal and external parties, Availability of adequate human resources, Availability of adequate facilities and infrastructure. support, Available budget and Support from parents. While the inhibiting factors are: Not all students have cellphones, lack of internet quota, bad signal constraints and lack of enthusiasm for students.